2006
DOI: 10.1029/2006gl026776
|View full text |Cite
|
Sign up to set email alerts
|

Anoxia and high primary production in the Paleogene central Arctic Ocean: First detailed records from Lomonosov Ridge

Abstract: Except for a few discontinuous fragments of the Late Cretaceous/Early Cenozoic climate history and depositional environment, the paleoenvironmental evolution of the pre‐Neogene central Arctic Ocean was virtually unknown prior to the IODP Expedition 302 (Arctic Ocean Coring Expedition–ACEX) drilling campaign on Lomonosov Ridge in 2004. Here we present detailed organic carbon (OC) records from the entire ca. 200 m thick Paleogene OC‐rich section of the ACEX drill sites. These records indicate euxinic “Black Sea‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
217
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(234 citation statements)
references
References 31 publications
(66 reference statements)
17
217
0
Order By: Relevance
“…The highest concentrations (up to 14%) occur in the lower part of the short, lower Miocene "zebra" subunit (1/5), a few meters below the abrupt change into ventilated conditions, which was initiated by a critical tectonic threshold during the early Miocenethe opening of the Fram Strait [46]. Judging from ratios of carbon and sulfur concentrations, Stein et al [47] concluded that euxinic conditions began shortly after the PETM event and lasted Throughout the, ca. 10 Myr long early to middle Eocene interval.…”
Section: Paleoceanographic Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The highest concentrations (up to 14%) occur in the lower part of the short, lower Miocene "zebra" subunit (1/5), a few meters below the abrupt change into ventilated conditions, which was initiated by a critical tectonic threshold during the early Miocenethe opening of the Fram Strait [46]. Judging from ratios of carbon and sulfur concentrations, Stein et al [47] concluded that euxinic conditions began shortly after the PETM event and lasted Throughout the, ca. 10 Myr long early to middle Eocene interval.…”
Section: Paleoceanographic Resultsmentioning
confidence: 99%
“…Previously, this event had been suggested by [47] based on δ13C data generated from organic matter. Sluijs et al [58] employed XRF scans to demonstrate cyclic variations in element concentrations in sediments older than ETM2.…”
Section: Paleoceanographic Resultsmentioning
confidence: 99%
See 3 more Smart Citations